2019
DOI: 10.1080/17436753.2019.1664793
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and dielectric properties of low-loss Zr-doped barium strontium titanate materials

Abstract: A series of materials of the composition Ba 0.7 Sr 0.3 Zr x Ti (1 − x) O 3 (BSZT), where x = 0.00, 0.01, 0.02 and 0.03, were synthesised through the sol-gel method whereupon the manifestations of partial substitution of Ti 4+ by Zr 4+ on the structural and dielectric behaviour of Ba 0.7 Sr 0.3 TiO 3 (BST) were studied. X-ray diffraction patterns of all samples showed the development of a single-phase crystalline perovskite structure. The dielectric behaviour of the ceramic samples has been studied in detail in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
(41 reference statements)
0
8
1
3
Order By: Relevance
“…A dip in the pure tetragonal‐BT is always found near 180 cm −1 which indicates the ferroelectric behavior, which was not observed in present case, indicating the formation of paraelectric phase; however, broadening in the peak ∼300 cm −1 was found which indicates that there is no long‐range ferroelectric order because a sharp peak is generally observed in tetragonal‐BT as reported . The broad bands near 508 and 573 cm −1 tend to diffuse with increase in x which may be due to decreasing concentration of Mg 2+ which is due to decreasing concentration of MgO 6 octahedra . It was also reported that the Raman active mode at 770 cm −1 , associated to the breathing of BO 6 octahedra .…”
Section: Resultscontrasting
confidence: 38%
“…A dip in the pure tetragonal‐BT is always found near 180 cm −1 which indicates the ferroelectric behavior, which was not observed in present case, indicating the formation of paraelectric phase; however, broadening in the peak ∼300 cm −1 was found which indicates that there is no long‐range ferroelectric order because a sharp peak is generally observed in tetragonal‐BT as reported . The broad bands near 508 and 573 cm −1 tend to diffuse with increase in x which may be due to decreasing concentration of Mg 2+ which is due to decreasing concentration of MgO 6 octahedra . It was also reported that the Raman active mode at 770 cm −1 , associated to the breathing of BO 6 octahedra .…”
Section: Resultscontrasting
confidence: 38%
“…However, these dipoles do not get appreciable time for alignment at high frequency, and only electronic polarization prevails under higher frequency regions (1KHz‐10 MHz). [ 33 ] Thus, the plot of dielectric constant (ɛ) and dielectric loss (tanδ) exhibits decreasing trend with increasing frequency. Here, lower loading of ZnO@APTES (30 vol%) produces the highest dielectric constant around 34.53 with low tanδ of 0.13.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26 ] A weak band at 1430 cm −1 pertains to ‐COOH, from the remnants of organic matter in the sol‐gel derived powders. [ 27 ] In the spectra of pure PS and the different formulated PZT/PS composites, the absorption peaks in the 2800‐3100 cm −1 range are attributed to the C‐H stretching vibrations in the benzene rings. The aromatic C=C vibrations show corresponding peaks at 1601, 1492, and 1451 cm −1 .…”
Section: Resultsmentioning
confidence: 99%